Pesan Dakwah dalam Film Animasi Nussa dan Rara Episode 1-5 (Analisis Semiotika Roland Barthes) - Nur Aini (MUKASI: Jurnal Ilmu Komunikasi, 2023)
This film is an animated da'wah packaged with the aim of teaching Islamic values that contain positive educational messages for children. Rara tells the story of a little sister who is curious about many things. Nussa as a patient, loving sister and always gives good advice to her sister. The purpose of this study was to determine the message of da'wah contained in the animated film Nussa and Rara. The method used is the semiotic analysis method of Roland Barthes because this method is classified as suitable for analyzing the da'wah message contained in the animated film Nussa and Rara, namely denotation and connotation. The overall results of this study include; how to behave before bed that must be done for every Muslim, starting all work by reading basmalah, giving a smile to our brothers because smiling is the easiest worship, cleaning the surrounding environment to create a comfortable and beautiful atmosphere, and when the call to prayer is resounding don't be noisy because Adhan is a call from Allah that must be hastened. Episodes 1-5 contain da'wah messages that can be a teaching for the general public about Islamic teachings.